Hedonic and eudaimonic well-being for sustainable development in university students: personality traits or acceptance of change? - Di Fabio, Annamaria; Palazzeschi, Letizia; Bonfiglio, Antonia; Gori, Alessio; Svicher, Andrea (Frontiers in Psychology, 2023)
The psychology of sustainability and sustainable development is aimed at providing contributions to the establishment of a culture of sustainability regarding the 2030 Agenda for the 17 sustainable development goals. In this framework, this study examines the associations between acceptance of change and well-being (hedonic and eudaimonic sides), controlling for the effects of personality traits, in 284 Italian university students. Acceptance of change explained additional variance over personality traits in relation to hedonic and eudaimonic well-being. Acceptance of change could thus represent a promising resource for well-being in strength-based prevention perspectives, opening future perspectives to face the challenges of sustainable development, particularly with respect to the goal 3 “Good health and well-being” of the Agenda 2030.